Hierarchically structured copper current collectors via green laser activation: A silver-benchmarked solution for all-printed microsupercapacitors - Jo, Yejin; Bae, Sang Hyeok; Cho, Yong Jun; Baek, Beomjung; Kim, Dong Young; Hong, Seok Jin; Jo, Hyeon Chan; Cho, Min Kyung; Park, Jung Hwan; Jeong, Sunho (Elsevier BV, 2025)
By engineering hierarchical Cu particles composed of Cu nanoparticle monolayer-adsorbed Cu flakes and utilizing green laser irradiation, we achieved in situ formation of an ultrathin carbon passivation layer that ensures both electrical conductivity and electrochemical stability. The printed Cu current collectors exhibit an exceptional conductivity of 243,500 S m−1, surpassing printed Ni and carbon-based current collectors and approaching that of printed Ag current collectors. The resulting microsupercapacitor, fabricated with ionic liquid electrolytes, operated stably within a potential window of up to 1.5 V, as a cost-effective benchmark alternative to expensive Ag-based current collector. A long-term cycling stability (>98 % over 6000 cycles) was confirmed with chronoamperometry measurement at a constant voltage of 3.75 V (vs. Li/Li+) in conjunction with depth profiling XPS analysis. Photothermal simulations revealed that a uniform heat distribution in hierarchical Cu particles enables comprehensive photothermal reactions, including surface oxide removal, interparticle sintering, and in situ carbon passivation. Comparative analyses with Ag- and Ni-based current collectors further highlighted the superior performance and scalability of laser-activated and printed Cu current collectors, suggesting a viable pathway toward sustainable, low-cost energy storage devices integrated with form-factor-free electronics.